Water resources planning to water transfers to modernization of an irrigation district: Oakdale Irrigation District case study - Knell, Steven R., author; Eldridge, Gregory W., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2012)
Oakdale Irrigation District (OID) was formed in 1909 and provides pre-1914 water rights to over 55,000 acres of irrigated farmland located within the northern San Joaquin Valley of California. The district's situation is similar to many irrigation districts in the Central Valley; it has an aged and often failing infrastructure which has had little investment over the years; it has an intermixed customer base of both urbanizing ranchette lands, expanding dairies and a rapid conversion to high value permanent crops; it has a demand for more flexible water deliveries and services from its customers; and has limited financial resources to meet those demands. With that backdrop, initiated in November 2004 and completed in June 2007, OID developed a Water Resources Plan (WRP) as a strategic roadmap for addressing those issues. Today the district is moving forward with the implementation of a $170 million capital improvement program to meet the multifaceted needs of the district. Those needs as outlined in the WRP include the protection of the District's water rights; an increase in agricultural water supply reliability during droughts; protection for the local areas surface and groundwater supplies; along with a roadmap to modernize and rebuild a century old system to meet the needs of its changing customer base. Regional water transfers are being used as the basic funding mechanism to make it all happen. The paper will provide a background of the drivers that got the OID to begin the planning process; it will discuss how the planning process evolved; what the findings and recommendations were in the final Water Resources Plan (WRP); and finally, how those recommendations are being moved forward to implementation.
Irrigated agriculture responds to water use challenges
Planning, transfers and modernization
Presented at Irrigated agriculture responds to water use challenges - strategies for success: USCID water management conference held on April 3-6, 2012 in Austin, Texas.